2011
DOI: 10.1016/j.freeradbiomed.2011.04.042
|View full text |Cite
|
Sign up to set email alerts
|

Inorganic nitrite therapy: historical perspective and future directions

Abstract: Over the past several years, investigators studying nitric oxide (NO) biology and metabolism have come to learn that the one electron oxidation product of NO, nitrite anion, serves as a unique player in modulating tissue NO bioavailability. Numerous studies have examined how this oxidized metabolite of NO can act as a salvage pathway for maintaining NO equivalents through multiple reduction mechanisms in permissive tissue environments. Moreover, it is now clear that nitrite anion production and distribution th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
92
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(97 citation statements)
references
References 267 publications
2
92
1
2
Order By: Relevance
“…Close correlation between plasma and tissue nitrite after nitrite administration has been previously reported [24]. Similar to our results, Raat et al [8] have reported a direct correlation between plasma and liver nitrite concentrations; some authors have suggested that high correlation between serum and some tissue NO x indicates non-specific accumulation of NO x in these organs [27] while others suggest that anion transporters aid regulated and tissue-specific transport of nitrite across cell membranes [24,28].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Close correlation between plasma and tissue nitrite after nitrite administration has been previously reported [24]. Similar to our results, Raat et al [8] have reported a direct correlation between plasma and liver nitrite concentrations; some authors have suggested that high correlation between serum and some tissue NO x indicates non-specific accumulation of NO x in these organs [27] while others suggest that anion transporters aid regulated and tissue-specific transport of nitrite across cell membranes [24,28].…”
Section: Discussionsupporting
confidence: 91%
“…The changes we observed in stomach and liver NO x contents following nitrate administration were different; it has been reported that differences in nitrite concentrations between tissues may reflect the degree of NOS activity and the oxidation pathways of NO [24]; however, increased NO x content of the stomach following nitrate administration may also be attributed in part to nitrate absorption from the stomach [25].…”
Section: Discussioncontrasting
confidence: 69%
“…However, it is now recognized that nitrite plays important roles in various physiological processes, such as blood pressure control, hypoxic vasodilation, and the inhibition of platelet activation, and its use is being explored for various therapeutic applications (2)(3)(4). For example, administration of nitrite by infusion has been shown to increase blood flow, and its physiological administration through dietary nitrate has been shown to decrease blood pressure (5)(6)(7)(8)(9)(10).…”
mentioning
confidence: 99%
“…The use of sodium nitrite (NaNO 2 ) can be dated back as early as 850 B.C., when it was employed in the meat curing process [1]. It was also used to impart flavor and color to preserved meat [2], and thus had been widely used as a food additive [3].…”
Section: Introductionmentioning
confidence: 99%
“…In the early 20th century, it was suggested that nitrite might increase the incidence of cancer, and the toxic nature of high nitrite levels had since been confirmed [4] [5]. However, nitrites are also used in the medicinal field [6] and sodium nitrite may have therapeutic potential as a nitric oxide (NO) prodrug in the treatment of tumors, allowing a transient increase in the delivery and efficacy of anti-cancer drugs [1]. To better understand the mechanism under which nitrite-mediated therapy affects tumor progression and development, direct investigation of the effect of sodium nitrite on carcinogenesis, both in vitro and in vivo, is paramount.…”
Section: Introductionmentioning
confidence: 99%